CUSTOMER LOYALTY PERSPECTIVE DEVELOPED FROM CUSTOMER COMMITMENT - Denis Fidita Karya (Universitas Dinamika, 2020)
This article discusses various aspects of relationship marketing ranging from the benefits of customer retention marketing strategies for the survival of the company to developments that can be done to transform customer retention into customer loyalty. This article also discusses customer recall management as an effort to create and maintain customer loyalty. This is because the effort to create and maintain customer loyalty is an important capital for the company to be able to survive in an increasingly competitive market competition. This is relevant to the view that the main purpose of customer retention efforts is to create and develop relationships with customers based on added value. This article can be used as a basic perspective for further research that examines customer relationship management, especially in the aspect of developing customer loyalty.